Demand and selection effects in supplemental health insurance in Germany - Renate Lange; Jörg Schiller; Petra Steinorth (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper empirically assesses the selection effects and determinants of the demand for supple-mental health insurance that covers hospital and dental benefits in Germany. Our representative dataset provides doctor-diagnosed indicators of the individual's health status, risk attitude, demand for medical services and insurance purchases in other lines of insurance as well as rich demographic and socioeconomic information. Controlling for a wide range of individual preferences, we find evidence of adverse selection for individuals aged 65 and younger for hospital coverage despite initial individual underwriting by insurers. The reverse is true for individuals older than 65; individuals with supplemental hospital coverage are healthier on average. In addition, insurance affinity and income are the most important drivers of the demand for both types of coverage.
Keywords: D82; G22; I11; 330; supplemental health insurance; adverse selection; insurance demand; German Statutory Health Insurance; insurance affinity